Combination Therapy Slow Deep Breathing and Acupressure to Overcome Ineffective Breathing Pattern Nursing Problems: A Case Study - Kushariyadi; Faiqoh Salsabillah Ufaidah; Rondhianto; Eka Yufi Septriana Candra (Nursing and Health Sciences Journal (NHSJ), 2023)
Therapy slow deep breathing exercise and acupressure is a complementary therapy that aims to reduce the symptoms of the disease to improve the quality of individual health. Complementary therapy is rarely done in hospitals so that the symptoms felt by patients are not reduced without medication. This therapy can reduce the symptoms of shortness of breath in patients who specifically experience impaired breathing patterns that are not effective. The study aims to determine the effectiveness of combination therapy slow deep breathing exercises and acupressure to address ineffective breathing pattern nursing problems in nursing care. This type of research is a case study using the nursing care method. The research sample was patients treated in the Gardena room at dr. Soebandi General Hospital Jember. Patients were given nursing interventions in the form of a combination of slow deep breathing exercise therapy and acupressure for 1-2 times a day for 3 days. Providing nursing interventions in the form of a combination of slow deep breathing exercise therapy and acupressure can overcome ineffective breathing pattern nursing problems. This is indicated by the improvement in the patient's condition that the shortness of breath is reduced, the frequency is improving, not using the auxiliary muscles of breathing, and the depth of breathing is improving. Patients can also carry out the therapy independently properly and correctly. A combination of slow deep breathing exercise therapy and acupressure can overcome the problem of ineffective breathing pattern nursing.